Transcriptome analysis and physiological changes in the leaves of two Bromus inermis L. genotypes in response to salt stress - Song, Wenxue; Gao, Xueqin; Li, Huiping; Li, Shuxia; Wang, Jing; Wang, Xing; Wang, Tongrui; Ye, Yunong; Hu, Pengfei; Li, Xiaohong; Fu, Bingzhe (Frontiers in Plant Science, 2023)
Soil salinity is a major factor threatening the production of crop around the world. Smooth bromegrass (Bromus inermis L.) is a high-quality grass in northern and northwestern of China.Currently, selecting and utilizing salt-tolerant genotypes is an important way to mitigate the detrimental effects of salinity on crop productivity. In our research, salt-tolerant and salt-sensitive varieties were selected from 57 accessions based on a comprehensive evaluation of 22 relevant indexes, and their salt-tolerance physiological and molecular mechanisms were further analyzed.Results showed significant differences in salt tolerance between 57 genotypes, with Q25 and Q46 were considered to be the most salt-tolerant and salt-sensitive accessions compared to other varieties, respectively. Under saline condition, the salt-tolerant genotype Q25 not only maintained significantly higher photosynthetic performance, leaf relative water content (RWC) and proline content, but also exhibited obviously lower relative conductivity and malondialdehyde (MDA) content than the salt-sensitive Q46 (P<0.05). The transcriptome sequencing indicated that 15,128 different expression genes (DEGs) in Q46, of which 7,885 were upregulated and 7,243 downregulated, and 12,658 DEGs in Q25, of which 6,059 were upregulated and 6,599 downregulated. KEGG analysis showed that the salt response differences between Q25 and Q46 were attributed to the variable expression of genes associated with plant hormone signal transduction and MAPK signaling pathway. Furthermore, a large number of candidate genes, related to salt tolerance, were detected, which involved in transcription factors (zinc finger proteins) and accumulation compatible osmolytes process (Glutathione S-transferases, pyrroline-5-carboxylate reductases), etc. This study offers an important view of the physiological and molecular regulatory mechanisms of salt tolerance in two smooth bromegrass genotypes, and lays the foundation for further identification of key genes linked to salt tolerance.